Assessment of Tax Compliance Costs for Businesses in the Kyrgyz Republic - World Bank Group (World Bank, Bishkek, 2018)
The International Finance Corporation (IFC), a member of the World Bank Group, is the largest global development institute focused on supporting the private sector in emerging economies. Through its work with more than 2,000 companies worldwide, IFC mobilizes capital, expertise, and influence to create markets and opportunities for developing countries. The objective of the IFC Central Asia Tax Project is to improve compliance with mandatory requirements of tax legislation through increased transparency and simplification of tax administration procedures. Simplification of tax accounting procedures will reduce costs of tax compliance, lessen the administrative burden on small and medium businesses, reduce barriers to entry into the formal economy, and serve as a driver for economic growth in the Kyrgyz Republic. The key element of reforms is an immediate assessment of their efficiency and possibility for adjustments based on assessment results. With this view, IFC, through its technical assistance tax reforms projects, has conducted a series of studies, which help monitor the tax system reforming processes in the Kyrgyz Republic. The main goal of the studies was a periodic assessment of time and costs to taxpayers in the Kyrgyz Republic in complying with the mandatory requirements of the tax legislation. Equitable intervals of measurements allowed an immediate assessment of the impact of implemented tax reforms on the cost of taxpayers to comply with tax legislation. In addition, actual data on the tax system status helped elaborate concise recommendations for the Government with the focus on elimination of identified issues and reduction of the tax administration costs to businesses. This report outlines the results of all three rounds of business environment surveys in the area of tax regulation; it includes the estimates of tax accounting costs of taxpayers in the Kyrgyz Republic in 2012, 2014, and 2016.